Portrait of Political Campaign Violations at the 2019 General Elections in Pekanbaru - Nabella Pusparani; Natasya Assyura Putri; Delfy Agustina; Defy Rizky Ramadhany; Zullivi Muhardila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
This study discusses election violations in 2019, which occurred in Pekanbaru. Six reports found to Election Supervisory Agency (BAWASLU), but none of these reports was followed up by BAWASLU. This phenomenon is the basis for the researcher to conduct a study of election violations in Pekanbaru to identify the forms of violations that occur. This study uses a descriptive qualitative approach and selects the informants with purposive sampling. The data obtained from interviews with the Election Supervisory Agency Pekanbaru. The results of this study indicate that the form of violations that occur are indications of money politics committed by candidates, and there is a successful team conducting a campaign process during the quiet period.